Depression, anxiety symptoms, Insomnia, and coping during the COVID-19 pandemic period among individuals living with disabilities in Ethiopia, 2020 - Necho, Mogesie; Birkie, Mengesha; Gelaye, Habitam; Beyene, Abeba; Belete, Asmare; Tsehay, Mekonnen (PloS one, 2020)
People with disabilities face multiple barriers that prevent them from accessing care and essential information related to the COVID-19 pandemic that poses additional stress and psychopathology. Therefore, the investigation of psychopathologies during the COVID-19 outbreak and emergency response is critical. A cross-sectional survey was implemented from July 15/2020 to July 30/2020. The PHQ-9, GAD-7 scale, insomnia severity index-7, and brief resilient coping scale were administered to participants. The collected data was then entered into Epi-data version 3.1 and exported to SPSS-20 for analysis. Descriptive statistical procedures were employed to describe the various psychopathologies. A binary logistic regression method was used to identify the related factors for the psychopathologies. Furthermore, an odds ratio with its 95%CI was driven to show association strength, and a P-value <0.05 was declared as statistically significant. A significant proportion of individuals living with disability had psychopathologies; 46.2% for depression symptoms, 48.1% for generalized anxiety disorder symptoms, and 71% for insomnia symptoms. Nearly 45.7% of participants were low resilient copers to their psychopathology. Depression was significantly higher in divorced/widowed/separated (AOR = 3.4, 95% CI: 1.28-8.92, P-value = 0.006), non-educated (AOR = 2.12, 95% CI: 1.12, 5.90, P-value = 0.001), and unemployed (AOR = 2.1, 95% CI: 1.32, 5.11, P-value = 0.005) as well as a daily laborer (AOR = 2.4, 95% CI: 1.20, 4.89, P-value = 0.014) subjects. Generalized anxiety disorder was also significantly higher in young age (<40 years) (AOR = 1.7, 95% CI: 1.32, 2.98, P-value = 0.02), single (AOR = 2.3, 95% CI: 1.24, 5.3, P-value = 0.011), widowed/divorced/separated (AOR = 1.5, 95% CI: 1.12, 2.78, P-value = 0.032), preparatory school completed (AOR = 3.00, 95% CI: 1.59, 5.46, P-value = 0.001), daily laborer (AOR = 2.7, 95% CI: 1.21, 5.23, P-value = 0.003), and unemployed (AOR = 2.5, 95% CI: 1.17, 4.78, P-value = 0.005) participants. Moreover, insomnia was significantly higher in single (AOR = 1.5, 95% CI: 1.12, 3.09, P-value = 0.027), divorced/widowed/separated(AOR = 6.2, 95% CI: 1.08, 11.29, P-value = 0.032), unemployed (AOR = 3.00, 95% CI: 1.22, 7.03, P-value = 0.001), blind (AOR = 2.8, 95% CI: 1.42, 6.35, P-value = 0.001), and deaf (AOR = 10.2, 95% CI: 4.52, 35.33, P-value = 0.002) participants. Depression, anxiety, and insomnia were highly prevalent among individuals with a disability during the COVID-19 period. Multiple sociodemographic and disability-related factors were associated with this high psychopathology. Attention has to be given by the government and other stakeholders to intervene in psychopathology and its associated factors.